Non-polar lipid from greenshell mussel (Perna canaliculus) inhibits osteoclast differentiation - Siriarchavatana P; Kruger MC; Miller MR; Tian HS; Wolber FM (Elsevier Inc, 2021)
The osteoclast-dependent bone resorption process is a crucial part of the bone regulatory system. The excessive function of osteoclasts can cause diseases of bone, joint, and other tissues such as osteoporosis and osteoarthritis. Greenshell mussel oil (GSM), a good source of long chain omega-3 polyunsaturated fatty acids (LCn-3PUFAs), was fractionated into total lipid, polar lipid, and non-polar lipid components and their anti-osteoclastogenic activity tested in RAW 264.7 cell cultures. Osteoclast differentiation process was achieved after 5 days of incubation with RANKL in 24-well culture plates. Introducing the non-polar lipid fraction into the culture caused a lack of cell differentiation, and a reduction in tartrate-resistant acid phosphatase (TRAP) activity and TRAP cell numbers in a dose-dependent manner (50% reduction at the concentration of 20 μg/mL, p < 0.001). Moreover, actin ring formation was significantly diminished by non-polar lipids at 10-20 μg/mL. The bone digestive enzymes released by osteoclasts into the pit formation were also compromised by downregulating gene expression of cathepsin K, carbonic anhydrase II (CA II), matrix metalloproteinase 9 (MMP-9), and nuclear factor of activated T-cells, cytoplasmic 1 (NFATc1). This study revealed that the non-polar lipid fraction of GSM oil contains bioactive substances which possess potent anti-osteoclastogenic activity.
This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: AA, Arachidonic acid; ALA, Alpha linolenic acid; CAII, Carbonic anhydrase II; DHA, Docosahexaenoic acid; DMSO, dimethyl sulfoxide; DPA, Docosapentaenoic acid; EPA, Eicosapentaenoic acid; FFAR, Free fatty acid receptor; GSM, Greenshell mussel; Greenshell mussel; LA, Linoleic acid; LPS, Lipopolysaccharide; MMP-9, Matrix metalloproteinase 9; MUFA, Monounsaturated fatty acid; NF-κB, Nuclear factor κB; NFATc1, Nuclear factor of activated T-cells, cytoplasmic 1; OA, Osteoarthritis; Omega 3 fatty acid; Osteoarthritis; Osteoclasts; Osteoporosis; PA, Palmitic acid; PPAR, Peroxisome proliferator activated receptor; PUFA, Polyunsaturated fatty acid; RANKL, Receptor activator of nuclear factor κB ligand; SFA, Saturated fatty acid; TRAP, Tartrate-resistant acid phosphatase